THE GENETIC POTENCY OF PLANTAIN AGUNG SEMERU VARIETY FROM LUMAJANG REGENCY EAST JAVA INDONESIA - Prahardini, P.E.R. (El-Hayah : Jurnal Biologi, 2009)
Lumajang regency is one of the banana production centre in East Java having high- diversity of banana germ plasm.  There are 33 cultivars of  banana germ plasm in the regency,   consist of eaten ripe and plantain. One of uniqe plantain used as the symbol of Lumajang regency is plantain Agung Semeru variety, the local superior variety of this regency.  This variety can grow well at 450 – 650 m above sea level.  The uniqueness of banana Agung Semeru variety can be seen by the number of sucker per cluster (only   1 – 2  suckers per cluster), the size of the finger (33 – 36 cm long and  19 cm around) and the number of hand per bunch (only 1 – 2 hand per bunch).  Other characteristics of the variety are the thickness of fruit skin, the long period of fruit storage  (3 – 4 weeks after harvesting) and  the sweetness of fruit flesh. Even though the skin changes from yellow to black,  the flesh still  can be consumed, because it  doesn’t become soft. This variety also resistant to the  Sigatoka disease compared to other plantain cultivars.